Quasi-Newton methods for solving non-smooth multiobjective optimization - Najmeh Hoseini Monjezi (Journal of Mathematical Extension, 2014)
In this paper, a quasi-Newton type algorithm for non-smooth multiobjective optimization is presented. In this algorithm, in every iteration a quadratic subproblem solves until a critical point is reached. Moreover, the global convergence of the algorithm is established under suitable assumptions